The relationship between gastric microbiome features and responses to neoadjuvant chemotherapy in gastric cancer - Zhang, Peng; Xu, Jianfei; Zhou, Yanbing (Frontiers in Microbiology, 2024)
Background: Emerging evidence demonstrates that the gastrointestinal microbiome has the potential to be a biomarker in neoadjuvant chemoradiotherapy for colorectal cancer (CRC). Yet studies on the impact of the gastric microbiome (GM) on the response to neoadjuvant chemotherapy (NACT) are still scarce.Methods: Forty-eight patients with gastric cancer participated in this retrospective study, and 16S RNA sequencing was performed to evaluate formalin-fixed and paraffinembedded (FFPE) tissue biospecimens and fresh-frozen tissues.Results: In this study, 16 bacterial taxa at different levels, including Bacillus, Anaerococcus, and Chloroflexi, were identified to be enriched before NACT in response (R) patients in group FFPE. In contrast, 6 bacterial taxa, such as Haemophilus, Veillonellaceae (Veillonella), etc. were enriched after NACT, in which we reported for the first time that the phylum Chloroflexi was enriched before NACT in R patients.Thirty-one bacterial taxa of Coriobacteriaceae, Ruminococcaceae, Veillonellaceae, and Lachnospiraceae were identified in group mucosa as being enriched in R patients. In comparison, 4 bacterial taxa dominated by the phylum Proteobacteria were enriched in NR patients. Notably, the family Veillonellaceae was found in both tissue samples, and the metabolic pathways, including the citrate cycle (TCA cycle) and various amino acids, including alanine, were found to be potentially predictive in both sample species.Conclusions: There are differences in the features of the GM for different NACT response results. The causal relationship deserves to be confirmed by further investigations.